Réception de messages en sécurité routière : de l’empathie virtuelle aux réponses empathiques et cognitives - Pénélope Daignault; Marion Reny Delisle; Emmanuelle Gagné (Communiquer)
Firstly, we examined the relation between the personality trait of virtual empathy and empathic responses generated by six road safety messages based on a threat and produced in Quebec and in France. Secondly, we explored the way in which empathic responses are involved in information processing, as well as how the production context influences the intensity of empathic responses and the type of thoughts generated. The data analysis highlights the influence of the production context on the ability to project in the events presented. The Quebec announcements engendered stronger empathic responses.